HEALTH ASSESSMENT OF GOVERNMENT BANKS IN INDONESIA USING RISK-BASED BANK RATING - Melvina Permatasari; Peni Sawitri (Jurnal Ilmiah Ekonomi Bisnis, 2019)
Health of a bank can be defined as the ability of a bank to conduct banking operational normally and be able to satisfy all its obligations well by means of accordance with the applicable banking regulations. The health assessment is very important to a bank, because the bank managing public funds entrusted to the bank. Accordance with PBI 13/1/PBI/2011 numbers that have been set on January 5, 2011 and was implemented by the bank in July 2011, CAMELS method is no longer used as a method to measure the health of a bank. CAMELS method was replaced by RGEC method (Risk profile, Good Corporate Governance, Earnings, and Capital) to measure and assess the health of a bank. This research conducted on the four Government Banks (Bank Mandiri, BNI, BTN, and BTN) from the year 2009-2012 with comparative descriptive method. The results of Risk Profile factor that use analysis tool of NPL to measure Credit Risk showed that Bank Mandiri, BNI, BRI into category of healthy bank, while BTN decreased slightly in the rankings in 2012 from a healthy bank into fairly healthy bank. Meanwhile the assessment results of liquidity risk that calculated use analysis tool of LDR showed that Bank Mandiri and BNI into category of very healthy bank, BRI tend to stable with healthy bank category, but BTN into category of poorly bank. The result of self-assessment Good Corporate Governance showed that four Government Banks have been successfully implemented Good Corporate Governance very well. The result of Earnings factor that use analysis tool of ROA showed that four Government Banks as healthy bank. The result of Capital factor that use analysis tool of CAR generally showed that four Government Banks into category of very healthy bank.